Inhibitory effect of clove oil nanoemulsion on fumonisin isolated from maize kernels. (December 2020) - Singh, Priyanka; Dasgupta, Nandita; Singh, Vineeta; Chandra Mishra, Narayan; Singh, Hemant; Purohit, Shiv Dutt; Srivastava, Nidhi; Ranjan, Shivendu; Yadav, Narayan Prasad; Mishra, Bhartendu Nath
Abstract: Fumonisins are an important class of mycotoxin due to its wide distribution, health hazard, and economic significance. In the current study, clove oil nanoemulsion was investigated to reduce the load of fumonisin from the maize kernels. The fabricated nanoemulsion of 103 nm size range efficiently reduced the growth of Fusarium proliferatum sp. and HPLC data confirms the reduction in the load of fumonisin B1 and B2 to the maximum recommended level by European Union. Further, clove oil nanoemulsion was electrosprayed to form a ready to use formulation with a core shell matrix. Denatured whey protein has been used as wall material and 96.25% encapsulation efficiencywas achieved. . The improved antifungal activity on maize kernel and ready-to-use prototype has future possibilities to be scaled up at industrial scale. Thus, the encapsulated material can be used as a preventive measure to reduce the fumonisin load during storage conditions. Graphical abstract: Image 1 Highlights: Clove oil nanoemulsion was fabricated by wash-out method. Nanoemulsion was further processed into powder form of size 103 nm by electrospray. The encapsulated material can inhibit fumonisin B1 and B2 in maize kernels. The product can reduce mycotoxin load during maize storage conditions.